2019
DOI: 10.1177/0144598719897422
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of regenerated roof and instability support control countermeasures in a steeply dipping working face

Abstract: Roof regeneration in coal mining occurs when the remaining bottom slice of thick coal is re-mined. In view of the challenges of roof fall and instability support of a regenerative roof in the mining of steeply dipping coal seams, combined with the geological and engineering conditions of the working face in the Panbei Coal Mine, the mechanism of the instability of the regenerative roof and support is studied, and control countermeasures are proposed. Based on the comprehensive combination of the measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…ey reported the temporal sequence and asymmetry in the dip direction, as well as their variations in different parts of the strike [22]. Our field monitoring data demonstrated that due to the influence of the dip angle, the distance between the caving gangue and support gradually increased from the bottom to the top along the working face [11]. is implies that the mined-out area is under a nonuniform filling state along the working face dip due to a steep dip angle since a nonzero angle β is formed by the floor/support and caving gangue/floor contact lines.…”
Section: Variation In the Support Load Bearing Characteristics Induced By The Spalling -Roof Collapse Hazard Chainmentioning
confidence: 73%
See 1 more Smart Citation
“…ey reported the temporal sequence and asymmetry in the dip direction, as well as their variations in different parts of the strike [22]. Our field monitoring data demonstrated that due to the influence of the dip angle, the distance between the caving gangue and support gradually increased from the bottom to the top along the working face [11]. is implies that the mined-out area is under a nonuniform filling state along the working face dip due to a steep dip angle since a nonzero angle β is formed by the floor/support and caving gangue/floor contact lines.…”
Section: Variation In the Support Load Bearing Characteristics Induced By The Spalling -Roof Collapse Hazard Chainmentioning
confidence: 73%
“…Since the recycling rate of the top-coal caving mining technique is quite low, the fully mechanized longwall mining of soft coal faces with large cutting heights has become a conventional technique for improving the high-efficiency recovery in thick SDCSs [11]. As the cutting height continues to rise, the stress concentration in the surrounding rock in the mined-out area gradually increases, the stress release space enlarges, and the magnitude and intensity of the surrounding rock movement grow [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of longwall caving mining in the SDCS, the roof movement, deformation, and failure characteristics are active in the middle and upper area along the inclined direction of the working face. The contact and loading characteristics of the roof and support in this area are complex, making the stability control of the "support surrounding rock" system more complicated and easy to cause safety accidents (Wu et al, 2014; Xie et al, 2018; Chi et al, 2020; Wu et al, 2021; Hu et al, 2021). The local filling mining technology of the SDCS longwall mining effectively bears the stress of surrounding rock, reduces the stress concentration, and influences the surrounding rock's range.…”
Section: Introductionmentioning
confidence: 99%
“…A finding regarding the distribution of mine pressure is asymmetric weighting along the dip direction of the working face during SDCS excavation (Yin et al 2010;Deng and Wang 2014;Yang et al 2015a, b;Chi et al 2020). Using the relationship between hydraulic support and surrounding rock, some researchers developed a mechanical model of the instability of support along the dip direction of the working face under different working states (Wu and Yun 1999;Wang and Jiao 2016;Yang et al 2018;Hu et al 2018;Chi et al 2019). Given that the breaking and migration features of the overlying strata are yet to be revealed accurately because of the undefined breaking process and the complexity of the SDCS mechanical features, the research progress in this direction can be reduced to the following achievements.…”
Section: Introductionmentioning
confidence: 99%